Creating a Circular Tower Defense Game: Development and Game Experience Measurement of Orbital Defense X - Asfarian, Auzi; Ramadhan, Wiradani; Putra, Widi Aryaguna; Raharjanto, Gabriel Muhammad; Frisky, Rakish (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2019)
In this paper, we propose a new style of tower defense game by using the circular placement of the tower. In this game, dubbed Orbital Defense X, the player must protect the earth with a circle of defensive tower circled around it. The game is developed using game development lifecycle from initiation phase through alpha version. To test the quality of the developed game, we measure the game experience using game experience questionnaire. The questionnaire is divided into three: core, social presence, and post-game questionnaire. The results show that male participant gains a significantly higher score than female participants. Overall, the game experience is received better by the male participant in the core and social presence components, with an average score of 2,27 vs 1,92 and 2,15 vs 1,86. However, in post-game experience, the female participant scores higher with 2,15 vs 1,95. The participant that previously played another tower defense game gave score more in the core, social presence, and post-game experience than the participant that haven’t played it before. Their score is 1,93 vs 2,37 in core, 1,67 vs 2,39 in social presence, and 2,07 vs 1,91 in post-game experience. The result also suggests for more attention in the challenge regarding the enemies (variety and difficulty) rather than more complex tower management system. The social ranking also suggested by the participant to improve the overall experience of this game.